WHITE SHIP SNOW WHITE SHIP (Archive of Conferences, 2021)
Genghis Aytmatov peoples writer of Kyrgyzstan (1968). Academician of the Kyrgyz Academy of Sciences (1974). He graduated from the Kyrgyz Agricultural Institute (1953) 1956-58 years is a listener of the higher literature course of the Writers Union of Moscow.